Urban landscape, sustainability and immigration in Santiago de Chile (Revista LIDER, 2020)
The bases of urban sustainability are structured over complexity, diversity and the mix of activities. However, in Chile, the development of urban landscape is driven by economic opportunity maneuvers that make urban structures. Besides, mobility, immigration and transculturation are building a new layer that favor the complexity of the urban landscape. This paper describes a method to map the intangible relations of immigration in a city that is not accustomed to the mixture, such as Santiago de Chile. Here the theoretical framework that drives the research and the first graphic display of this new urban layer is presented.